The schooling of students targeted to Special Education in Rural Education in the city of Boa Vista/RR - Edineide Rodrigues dos Santos; Maria Edith Romano Siems (Universidade Federal do Norte do Tocantins, 2020)
This article presents results of a research that aims to understand the schooling process, specifically for Special Education students in state rural schools for elementary and secondary schools located in the city of Boa Vista. Developed in the context of a master's degree in education, the research takes historical-dialectical materialism as a theoretical-methodological approach in the light of historical-critical pedagogy. The methodological procedure included re-reading the data generated based on observation, documentary research and interviews. Interviews were conducted with 15 teachers who worked with Special Education students in two rural schools in the municipality of Boa Vista. The results point out the lack of architectural, urbanistic, communication and transportation accessibility, that the Specialized Educational Service provided was not offered in accordance with legislation; that the Multifunctional Resource Rooms were not suitable for Specialized Educational Assistance and that most teachers had no training in the area of Special Education, contrary to what is prescribed in the current legislation. The survey also revealed that the majority of teachers longed for training in the area of Special Education and for decent working conditions, so that they could provide students with the appropriate knowledge.